URGENSI HARMONISASI POLA PROMOSI DAN MUTASI KEPANITERAAN LINGKUNGAN PERADILAN UMUM DAN AGAMA - Suhariyanto, Budi (Jurnal Hukum dan Peradilan, 2014)
There is a different registrar promotion pattern and mutation on general to religious court. Accordingly, important to get promotion pattern harmony and mutation to taking on this differences among of court (in particular general to religious court) under the supreme of court. Some efforts to consider are: (1). The equality of regulation or types of regulation on registrar promotion pattern and mutation (which is synchonized on the head desicion supreme of court. (2). The regulatory separation promotion pattern and judges mutation to registrar on the head desicion supreme of court. (3). Regulatory harmony on the registrar promotion and mutation. Keyword: function, career, registrar